The Natech risk associated to mining activity in Maramureş county, Romania - Nour Eugen; Smical Irina; Muntean Adriana (Zbornik Radova: Geografski Fakultet Univerziteta u Beogradu, 2015)
The Maramureş County is well-known as a strongly influenced area by mining exploitation of non-ferrous ores. To assess the Natech risk associated to tailing ponds in relation to climatic conditions and in particular to the rainfall in the area, four ponds with transboundary pollution potential were considered, namely: Aurul tailing pond, Novăţ tailing pond, Colbu 1 tailing pond and Colbu 2 tailing pond. In the methodology for the preliminary hazards analysis both historical accidents during 2000-2010 period and the conditions related to the construction and location of the tailing ponds were taken into account. Since the Novăţ taling pond, Colbu 1 tailing pond and Colbu 2 tailing pond are now preserved and permanently post-closure monitored, the transboundary risk has been estimated as being low. In these circumstances the Natech risk has been assessed only for the Aurul tailing pond which, at the present, is the only one active tailing pond in Maramureş County. The assessment results revealed a medium-high risk associated to the extreme meteo-climatic phenomena influenced by the regional climate changes.